2022
DOI: 10.1007/s11912-022-01252-w
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Phenotype/Lineage Leukemia: Has Anything Changed for 2021 on Diagnosis, Classification, and Treatment?

Abstract: Purpose of Review Recent advances in the small field of the rare mixed phenotype acute leukemias (MPAL) are presented focusing on a better understanding of their pathophysiology and search for better therapeutic approaches. Recent Findings Three aspects of respective classification, therapy, and immunophenotype of MPAL are reviewed. New proposals have been made to segregate MPAL subtypes based on their genomic landscape. In parallel, it was found that a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to investigate the clinical significance of isolated dim MPO expression in adult B/myeloid MPAL using the 2016 WHO classification, specifically the pattern of heterogenous antigen expression and intensity of MPO MPAL diagnosis is challenging because of the rarity of the disease, immunophenotypic diversity, and evolving diagnostic criteria. [1][2][3][4] The expression of MPO has been recognized as a specific marker of ently contradictory conclusions as to whether these entities are within the spectrum of B-ALL 8,9 or MPAL. 7 Our study assessed clinical and pathologic findings in adult patients with B/myeloid MPAL isoMPO and indicated that the clinical outcome of patients with B/myeloid MPAL i-soMPO was similar to patients with B-ALL but better than patients with other MPAL subtypes; B/myeloid MPAL isoMPO is thus better considered within the spectrum of B-ALL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first study to investigate the clinical significance of isolated dim MPO expression in adult B/myeloid MPAL using the 2016 WHO classification, specifically the pattern of heterogenous antigen expression and intensity of MPO MPAL diagnosis is challenging because of the rarity of the disease, immunophenotypic diversity, and evolving diagnostic criteria. [1][2][3][4] The expression of MPO has been recognized as a specific marker of ently contradictory conclusions as to whether these entities are within the spectrum of B-ALL 8,9 or MPAL. 7 Our study assessed clinical and pathologic findings in adult patients with B/myeloid MPAL isoMPO and indicated that the clinical outcome of patients with B/myeloid MPAL i-soMPO was similar to patients with B-ALL but better than patients with other MPAL subtypes; B/myeloid MPAL isoMPO is thus better considered within the spectrum of B-ALL.…”
Section: Discussionmentioning
confidence: 99%
“…MPAL diagnosis is challenging because of the rarity of the disease, immunophenotypic diversity, and evolving diagnostic criteria 1–4 . The expression of MPO has been recognized as a specific marker of myeloid/non‐monocytic lineage by the 2008 WHO classification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 B/T MPAL is exceptionally rare, consisting of 5% of MPAL. 8 As a specific marker for myeloid lineage, MPO is seldomly expressed in lymphoid leukemia, let alone in B/T MPAL. 1,5 Disseminated leukemic infiltrations across the body are unwonted.…”
mentioning
confidence: 99%